Human-mouse interspecies collagen I heterotrimer is functional during embryonic development of Mov13 mutant mouse embryos. - Wu, H (1990)
To investigate whether the human pro alpha 1(I) collagen chain could form an in vivo functional interspecies heterotrimer with the mouse pro alpha 2(I) collagen chain, we introduced the human COL1A1 gene into Mov13 mice which have a functional deletion of the endogenous COL1A1 gene. Transgenic mouse strains (HucI and HucII) carrying the human COL1A1 gene were first generated by microinjecting the COL1A1 gene into wild-type mouse embryos. Genetic evidence indicated that the transgene in the HucI strain was closely linked to the endogenous mouse COL1A1 gene and was X linked in the HucII transgenic strain. Northern (RNA) blot and S1 protection analyses showed that the transgene was expressed in the appropriate tissue-specific manner and as efficiently as the endogenous COL1A1 gene. HucII mice were crossed with Mov13 mice to transfer the human transgene into the mutant strain. Whereas homozygous Mov13 embryos die between days 13 and 14 of gestation, the presence of the transgene permitted apparently normal development of the mutant embryos to birth. This indicated that the mouse-human interspecies collagen I heterotrimer was functional in the animal. The rescue was, however, only partial, as all homozygotes died within 36 h after delivery, with signs of internal bleeding. This could have been due to a functional defect in the interspecies hybrid collagen. Extensive analysis failed to reveal any biochemical or morphological abnormalities of the collagen I molecules in Mov13-HucII embryos.(ABSTRACT TRUNCATED AT 250 WORDS)